KUALITAS BACAAN SURAH AL-FᾹTIḤAH IBU RUMAH TANGGA: (STUDI LIVING QUR’AN DI KELURAHAN GONDRONG, KOTA TANGGERANG) - Mawaddah, Amelia; Ulinnuha, Muhammad (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
In reciting the Al-Qur'an, it must be accompanied by quality recitation and tartil because it is a direct command from Allah SWT through his word in surah Al-Muzammil verse 4 which reads "Read the Al-Qur'an with superior tartil" and all can we do with a correct habit when reciting the verses of the Qur'an. However, it is very unfortunate that in this global era there are still many Qur'an illiterates around 72.25% who are unable to read the Qur'an, and of course this is very worrying for Muslims. This research is a Living Qur'an study using qualitative research methods in the form of phenomenology and descriptive analysis to analyze and describe the reading quality of surah Al-Fātiḥah for housewives using the Maisūrā Method approach as a benchmark for their reading. While the data collection techniques used are by means of tests, observations, interviews, and documentation.The results of this study are that of the 20 respondents who were successfully interviewed, there were 35% who had readings in a good category in reciting Surah Al-Fātiḥah tartil, then there were 35% who also had readings in the sufficient category, and finally there were 30% people who have less reading. All of this is due to intellectual factors and also the busyness of each housewife, which is different. Factors that support a housewife's ability to read the Koran are a strong intention and determination to study the Koran properly and correctly, support from the family, teachers who teach her to read the Koran, the environment sufficient social support, motivated by children and the surrounding environment, facilities and amenities for worship, and there are recitations by mothers who are followed diligently. While the factors that hinder the ability of housewives to read the Koran are low interest in learning the Koran, lack of support from the family, lack of motivation to study the Koran, not diligently attending recitations in assemblies, unsupportive surrounding environment, lack of knowledge of religion, and age that is no longer young.